The Politics of Personalised Medicine: Pharmacogenetics in the Clinic By Adam Hedgecoe - McGoey, L (2007)
The economy is back at the centre of sociological analysis. This, of course, only means that it has recaptured the position it once held in the works of the sociological ‘founding fathers’, Simmel, Pareto, Weber, Marx, and Durkheim.The so-called ‘new economic sociology’ (NES) is a field that grew out of studies made by US sociologists who essentially used three perspectives: cultural sociology, organizational sociology, and structural network sociology (Swedberg 1997). In addition, one could mention the political economic perspective and Bourdieu’s (2005) work. These last two, however, have been less important for the development of NES.More recently the idea of performativity has come into vogue (cf. Swedberg 2004). In this essay I review three books representing different economic-sociological perspectives drawn from the authors above: performativity, cultural sociology, and structuralism. The books, taken together, show the progress of the field, but they also point to its problems and shortcomings. They focus on the most central mechanism of the economy, markets, which for a long time have been the main issue of NES. The issue of the quality of the products found in markets is another common theme in the works reviewed. Finally I will discuss several major problems in today’s economic sociology, and suggest some strategies to improve the situation.